2021
DOI: 10.1016/j.cub.2021.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Explaining face representation in the primate brain using different computational models

Abstract: Explaining face representation in the primate brain using different computational models Highlights d The ability to explain responses of face cells is compared across multiple models d Active appearance model (AAM) outperforms all other models except CORnet-Z d Little additional variance could be explained by combining other models with AAM d A face-identification network ignores illumination and performs worse than others

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…It is worth noting that here we also explored other DNN models (Supplementary Fig. 5 ) and found that our findings could generalize to other DNNs (although as expected face-recognition performance was reduced in some DNNs that were not trained for face recognition), consistent with a previous report surveying a large class of DNN models for face representation 37 . Interestingly, a recent study has even shown that face-selective units can emerge from an untrained DNN 38 .…”
Section: Discussionsupporting
confidence: 90%
“…It is worth noting that here we also explored other DNN models (Supplementary Fig. 5 ) and found that our findings could generalize to other DNNs (although as expected face-recognition performance was reduced in some DNNs that were not trained for face recognition), consistent with a previous report surveying a large class of DNN models for face representation 37 . Interestingly, a recent study has even shown that face-selective units can emerge from an untrained DNN 38 .…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have successfully used DNN-based encoding models to characterize the tuning in category-selective visual areas and predict response patterns for a held-out test set. However, in these studies all image categories were represented in both the training and test set of the encoding model (Yamins et al , 2014; Güçlü and van Gerven, 2015; Kalfas, Kumar and Vogels, 2017; Murty et al , 2021), while some used only face images for both training and testing (Chang et al , 2021). For this reason, these studies cannot distinguish whether category selectivity in brain responses was determined by domain-specific features (e.g., face parts) that correlate well with DNN activations, or by domain-general image attributes that generalize across category boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…Studies investigating human face processing reported similarity to DCNNs, and, recently, a growing literature advocates the use of DCNNs as models to understand the neural basis of face processing in humans (Dobs et al, 2022; Grossman et al, 2019; Kuzovkin et al, 2018; Murty et al, 2021; Tsantani et al, 2021). However, correlations reported between DCNNs and neural representations of faces are often weak in humans (Kuzovkin et al, 2018; Tsantani et al, 2021), and a recent study has challenged how well DCNNs capture face representation in the macaque brain (Chang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%